Complicated clinical course of zoonotic tuberculosis due to Mycobacterium Caprae: A case report and literature review - Ata Yigit Çöllü; Nilay Uçarman; Gülsüm Iclal Bayhan (International Journal of Mycobacteriology, 2022)
The incidence of human tuberculosis (TB) disease due to Mycobacterium caprae, an etiologic agent of zoonotic TB along with Mycobacterium bovis, is very low. There are no guidelines for human TB caused by M. caprae, and treatment protocols for infections caused by this microorganism are based on the recommendations for M. bovis infections. We report a 15-year-old girl diagnosed with cervical lymphadenitis due to M. caprae. She did not recover completely despite 6 months of anti-TB medication. Therefore, treatment was extended to 12 months. There is a lack of information about the treatment of human M. caprae infections. Further studies evaluating the treatment in detail are needed.